Development and application of a new similar material for fluid–solid coupling model test - Bai, Jiwen; Wang, Meng; Zhang, Qing-Song; Zhu, Zhijing; Liu, Rentai; Li, Wei (Arabian journal of geosciences, 2020)
Correct selection of similar materials is key to geomechanical model tests. According to similarity theories, a novel similar material for the fluid–solid coupling model test was developed to solve problems of low similarity and poor stability. A similar material is mixed with calcium carbonate, white cement, paraffin, quartz sand, silicone oil, talc, and iron powder. Quartz sand and talc powder are the main materials; white cement, calcium carbonate, and paraffin are glue; silicone oil and iron powder are regulators. The effects of different mixing ratios on the compressive strength, permeability coefficient, and specific gravity were studied using a single factor analysis method. The main components controlling the material properties were determined through numerous laboratory tests. The experimental results show that the new material strength is controlled by cement, paraffin, and calcium carbonate. Its permeability coefficient can be adjusted by altering the ratio of silicone oil and paraffin. Its specific gravity is mainly affected by iron powder. The new material can simulate low-strength and medium-strength rock materials with different permeabilities, and it can effectively solve the problem that mechanical properties and nonhydrophilic properties cannot be satisfied simultaneously. The material was successfully applied in geological model tests of fault water inrush.